2020
DOI: 10.3390/ijms21124462
|View full text |Cite
|
Sign up to set email alerts
|

Connexin Hemichannels Contribute to the Activation of cAMP Signaling Pathway and Renin Production

Abstract: Connexin hemichannels play an important role in the control of cellular signaling and behaviors. Given that lowering extracellular Ca2+, a condition that activates hemichannels, is a well-characterized stimulator of renin in juxtaglomerular cells, we, therefore, tested a potential implication of hemichannels in the regulation of renin in As4.1 renin-secreting cells. Lowering extracellular Ca2+ induced hemichannel opening, which was associated with cAMP signaling pathway activation and increased renin productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…In our study, we found high Cx40 expression in the cortex of yotari mice in P4 and it was significantly higher in regard to wt, while consequently renin expression dramatically increased in the cortex of P14 yotari mice. This finding is in accordance with the previous report that disturbance of Cx40 intercellular signaling may lead to a disbalance of blood pressure control through renin secretion and hypertension onset [ 39 ]. Genetic loss-of-function defects of Cx40 in renal JG cells have been associated with renin-dependent hypertension [ 42 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In our study, we found high Cx40 expression in the cortex of yotari mice in P4 and it was significantly higher in regard to wt, while consequently renin expression dramatically increased in the cortex of P14 yotari mice. This finding is in accordance with the previous report that disturbance of Cx40 intercellular signaling may lead to a disbalance of blood pressure control through renin secretion and hypertension onset [ 39 ]. Genetic loss-of-function defects of Cx40 in renal JG cells have been associated with renin-dependent hypertension [ 42 ].…”
Section: Discussionsupporting
confidence: 94%
“…This provides a broader network of activity and intercellular communication concerning Cx control of renin secretion. Recently, Hong and Yao proposed that using strategies such as specific siRNA or Cxs mimetic peptides might lead to the development of more effective approaches in the control of renin secretion in vivo [ 39 ]. In the last decade, the role of gap junctions in the control of renin has been extensively investigated and multiple lines of evidence have shown that Cx40 channels are required for regulatory mechanisms of renin secretion and associated with correct localization of cells that express renin [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study, in which Cx40 was replaced by Cx45, however shows that not the expression of Cx40 itself is crucial for the regulation of renin release from juxtaglomerular cells but the gap junctional coupling with neighboring cells [ 98 ]. Moreover, not only cell–cell communication via gap junctions seems to be important for the regulation of renin secretion but also signaling via connexin hemichannels [ 36 ]. A recent study suggests that pannexin 1 could also be involved in the regulation of basal renin secretion through mediating intercellular communication [ 14 ].…”
Section: Identity Of Renin-expressing Cellsmentioning
confidence: 99%